The Galloway cattle - Mullen, Roger B. (My University, 1902)
Introduction: The Galloway cattle are a hardy hornless breed of beef cattle which take their names from the province of Galloway, which now comprises the stewarty of Kirk and Bright and the shire of Wigton but formerly included the shires of Ayrshire, Lanark, Reuben and Dumfries. The province now includes a strip of land about ninety miles long. It is a county which has high up lands richly covered with good pastures, and the valleys are very fertile, while the hills are densely covered with woods. Numerous small lakes and rivers are found along which are found rich moor lands. The climate while mild is damp and at times cold. 1st Theory of - Youdtt in his work on the cattle of G.B. says “There appears to be the remnants of two distinct breeds of native or aboriginal cattle. The first are middle horned while the second are polled. The Galloways, Augers, Suffolk and Norfolk breeds came from these polled cattle, while the Devon, Hereford, Sussex, and Highland breeds came from the horned cattle. 2nd Theory – The most plausible theory as to the origin of the Galloway Breed is that they were brought into Scotland, from Scythia through Europe and Ireland by the Scots who originally lived in Scythia. Herodotus, the historian, who wrote about B.C. 400 says, “In Scythia the oxen have no horns” and it is probable that the Galloways there came from the old Scythian breed of polled cattle. The believers of this latter theory account for the appearance of wild polled cattle in England by saying that in the comparative roving and uncertain life of the earlier settlers of Scotland led, their cattle would sometimes get lost in the forests, and as there was plenty of feed they thrived and thus started the wild breed. The difference in environment causing the different breeds to spring up.
Citation: Mullen, Roger B. The Galloway cattle. Senior thesis, Kansas State Agricultural College, 1902.
Morse Department of Special Collections
Keywords: Galloway Cattle; Cattle; History; Livestock; Animal Husbandry; Theses